Reabilitação fonoaudiológica da disfagia em pacientes pediátricos com tumor encefálico - Radzinsky, Tatiana Couto [UNIFESP] (2010)
Objective: To verify the efficacy of the dysphagia therapy performed by speech pathologists in pediatric patients with brain tumors using the Functional Oral Intake Scale (FOIS; Crary et al, 2005). Materials and Methods: The sample consisted children and adolescents with central nervous system tumors (23 male and 8 female), ages ranging from 11 months to 22 years old. Was performed a retrospective charts review of patients with central nervous system tumors and diagnosed oropharyngeal dysphagia, that were submitted to swallowing rehabilitation during internment period at the Pediatric Oncology Institute (IOP/GRAACC/UNIFESP) in the period from September 2003 to July 2009. To obtain the data, an evolution chart protocol was created, comprising patient’s identification, gender, initial diagnosis, underlying disease, injury site, speech-language diagnosis, specific tumor treatment, speech-language evaluation date, speech-language discharge date, number of speech-language therapy sessions, complications during the therapy period, respiratory conditions, and intubation period. Was used the Functional Oral Intake Scale (FOIS), a functional feeding evaluation scale, enabling to classify the patient according to the feeding intake (Crary, 2005). In addition, for speech-language diagnosis definition, and modified version of the Dysphagia Outcome and Severity Scale (O’Neil, 1999) was utilized. The scores were registered during the pre therapy period (speech-language functional evaluation) and post therapy. Improvement was considered when there was a change in the score to level 5 or higher, and decline when the score changed level 5 or lower. Results: All 31 patients showed improvement in the FOIS scale level after speech-language therapy. Level 5 or higher was achieved by 17 (54.8%) and was observed that 14 patients (45.2%) maintained the same FOIS level, not evolving as adequately. Results show that 19 patients (61.7%) presented severe dysphagia during the pre therapy period, out of those 11 (57.9%) managed to evolve to mild dysphagia, functional deglutition or normal deglutition. The dysphagia severity degree lowered in the post therapy on 21 patients (67.7%) while 10 (32.3%) maintained the same score. Conclusion: The patients that showed major improvement on the FOIS level had few clinical complications, tumors with better prognosis, and mean age of 12 years, whereas the patients that evolved in a less significant manner all presented clinical complications (decreased level of alertness and/or worsening of the clinical picture), tumors with bad prognosis (glioblastoma multiform stage IV, anaplasic ependymoma stage II, high-grade meduloblastoma, and brainstem glioma), in addition to mean age of 7.8 years.